Evaluation of pozzolanic activity and environmental assessment of cement composites with lubricating oil re-refining ash - Ramos da Silva, Alex [UNESP]; Friol Guedes de Paiva, Fábio; Henrique Pereira Silva, Lucas; Fernando dos Santos, Luis [UNESP]; Roefero Tolosa, Gabrieli [UNESP]; Eloizo Job, Aldo [UNESP]; Pérez Galvín, Adela; López-Uceda, Antonio; Rainho Teixeira, Silvio [UNESP]; Kinoshita, Angela; José dos Santos, Renivaldo [UNESP] (Elsevier, 2023)
Lubricant oil is considered a hazardous waste, and its disposal in the environment represents a high risk of damage to ecosystems. The purpose of this work is to study the feasibility of using lubricating oil re-refining ash (LORR) as a pozzolanic material in mortar composites with 0–40% of cement replaced by LORR, and determining the optimal content. Systematic experiments were performed to investigate the effects of LORR on the cementitious material properties, including workability, mechanical and flexural strength and water absorption. Furthermore, the hydration of the cement pastes was analyzed using thermogravimetric analysis (TGA) and X-ray diffraction (XRD). The results showed that LORR has high pozzolanic reactivity, increasing portlandite consumption, contributing to the additional formation of calcium silicate hydrate gel. Up to 30% LORR replacement resulted in similar mechanical properties to the control mortar. The leaching test showed that the raw LORR release 9 hazardous substances, including 6 heavy metals. The mortar proved to be effective for encapsulating all substances studied, in addition to contributing to the reduction of hazardous waste deposition in industrial landfills, and reducing the cost (less than24%) and embodied energy (less than29%) of eco-friendly cementitious materials. Therefore, the potential of lubricating oil re-refining ash for application in civil construction was demonstrated.
Keywords: Compressive strength; Eco-efficiency; Environmental assessment; Lubricating oil; Pozzolanic activity